Postmodern visions: consumer culture's (re)making of the gaze - Khanom, Afruza (BRAC University, 2011)
Contemporary societies have transformed traditional identities in such a way that we, as subjects of globalization and mass consumer culture, have become tremendously self-conscious of the ‘gaze’ which makes, breaks and molds us. Postmodern visions of (im) perfection reign on TV screens and other media which constitute the way others see us and we, in turn, see ourselves. In a postmodern world the self is, therefore, in constant flux in accordance with the language and images defined by consumer culture. This paper briefly discusses the effect of global consumerism as it enters into the social sphere, and also looks at the way the global aspect of consumerism has infiltrated the gaze emanating from Bangladeshi culture and tradition. It is thus creating, within the Bangladeshi subject, a site for consumer identity construction through which even traditional culture has become commodified.